The revised guidelines on the holding of referendums adopted by the Venice Commission - López Rubio, Daniel (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
In October 2020, revised guidelines on the holding of referendums were adopted by the Venice Commission, being the original ones approved back in 2007. Without discussing the convenience of introducing these mechanisms for citizen participation into the domestic law of the members of the European Council, the guidelines establish a set of legal guarantees that must be met by domestic law in order to respect Human Rights, democratic principles and the rule of law. We will thereby analyse the updates introduced on equal opportunities among the contending parties in referendum campaigns; the funding and transparency of such campaigns; the clarity of the question; or the inevitable respect for the constitutional framework by the call for a referendum.
Keywords: Referendum; popular initiative; direct democracy; clarity principle; Venice Commission; Rule of law